2021
DOI: 10.1080/21505594.2020.1869392
|View full text |Cite
|
Sign up to set email alerts
|

Type I interferons are essential while type II interferon is dispensable for protection against St. Louis encephalitis virus infection in the mouse brain

Abstract: St. Louis encephalitis virus (SLEV) is a neglected mosquito-borne flavivirus that causes severe neurological disease in humans. SLEV replication in the central nervous system (CNS) induces the local production of interferons (IFNs), which are attributed to host protection. The antiviral response to SLEV infection in the CNS is not completely understood, which led us to characterize the roles of IFNs using mouse models of St. Louis encephalitis. We infected mice deficient in type I IFN receptor (ABR −/-) or def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
2
2
0
1
Order By: Relevance
“…By contrast, no bioluminescent signal was detected in the control 129 mouse group, which remained healthy throughout the experiment ( Figure 4(B,C) ). These results are consistent with previous findings that type I IFN signaling control of flavivirus infection [ 32 ].
Figure 4.
…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…By contrast, no bioluminescent signal was detected in the control 129 mouse group, which remained healthy throughout the experiment ( Figure 4(B,C) ). These results are consistent with previous findings that type I IFN signaling control of flavivirus infection [ 32 ].
Figure 4.
…”
Section: Resultssupporting
confidence: 94%
“…4B and 4C). These results are consistent with previous findings that type I IFN signaling control of flavivirus infection (32).…”
Section: Establishment Of a Bli-based Animal Model Of Yel-avd And Yel-andsupporting
confidence: 94%
“…Thus, neutrophils are known to participate in severe neurological disease caused by SLEV, but it is unknown whether neutrophils contribute to protection or disease development. In accordance with in-vivo studies with other flaviviruses, mouse models of SLEV infection have shown that viral replication and access to the central nervous system are major factors in disease development, as absence of a functional type-I IFN response renders mice completely susceptible to SLEV infection, disease and death [ 98 ]. Excessive SLEV replication in the tissues of IFNAR −/− mice result in early and aggravated onset of neurological disease, including the production of the neutrophil-chemoattractant CXCL1 and increases in MPO levels in infected brains [ 95 , 98 ].…”
Section: Participation Of Neutrophils and Neutrophil-associated Molecules In Flaviviral Diseasesmentioning
confidence: 94%
“…Cell culture supernatant was collected at 48 h post-infection in dose-dependent assays of 7DMA, and 24 h post-infection in antiviral effect and cell viability assay for i7DMA. Viral loads were assessed using plaque-forming assays ( Rocha et al, 2021 ). Cell culture viability was assessed using MTT assays [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] according to recommendations from the manufacturer (Merck).…”
Section: Methodsmentioning
confidence: 99%